Potential endocrinedisruptor activity of drinking water samples - Solano, Marize de Lourdes Marzo [UNESP]; Raimundo, Cassiana Carolina Montagner; Vaccari, Carolina; Jardim, Wilson F.; Franci, Janete Aparecida Anselmo; Carolino, Ruither de O G; Luvizutto, João Francisco Lozano [UNESP]; Umbuzeiro, Gisela Aragão; Camargo, João Lauro Viana de [UNESP] (Taylor & Francis, 2015)
Conventional water treatment plants (WTP) do not completely remove contaminants with endocrine activity which may then be present in drinking water (DW). The potential for endocrine disruption of 2 DW samples collected in 2010 and 2012 from a conventional WTP in São Paulo, Brazil was investigated. In vivo assays were conducted with 21-day old female rats exposed to DW extracts for 3- (uterotrophic assay) or 20-days (pubertal assay). The exposure represented a daily ingestion of 2 L, 10 L and 20 L of DW per 60 kg-body weight. Caffeine (5.8 – 21 ug/L), estrone (1 ng/L), atrazine (2.2 – 11.2 ng/L), carbendazim (0.22 ng/L), azoxystrobin (0.23 ng/L), tebuconazole (0.19 ng/L) and imidacloprid (0.88 ng/L) were detected in DW extracts by LC-MS/MS. No increase in uterus wet weight in the uterotrophic assay, and no alteration of vaginal opening in the pubertal assay were observed. However, there were increased absolute blotted uterus weights in animals treated for 3-days with the 3 doses of both DW samples. LH and FSH levels showed significant dose-response increases in the uterotrophic assay using the 2010 DW sample, in association with a significantly increased incidence of vaginal keratinization after the 3-day exposure. The pubertal animals exposed to the 2010 DW had a significant body weight gain and decreased LH at the highest dose. Results suggest that DW samples tested exerted estrogenic and hypothalamic-hypophysis activity alterations in vivo.
Keywords: Emerging contaminants; Endocrine disruption; Pesticides; Pubertal female rat development; Uterotrophic assay